Upaya Peningkatan Pendapatan Industri Kecil Menengah Di Kota Tegal Dengan Pembuatan Toko Daring Berbasis Framework Codeigniter - Bakti, Very Kurnia; Rakhman, Arif (Jurnal Transformatika, 2018)
Based on some Small and Medium Industries (IKM) in Tegal City, almost all products from Small and Medium Industries (IKM) are marketed through classical transactions or conventional transaction models. There are still many producers who have not been able to promote and market their products online due to the absence online store facilities toward Small and Medium Industries (IKM) of Tegal City and the limited knowledge level of business managers about the utilization of information technology. Research will be conducted through several stages. Initial stages by collecting data - data from Small and Medium Industries (IKM) principal participants such as photos of its product, price lists, product specifications and others. Next stages is to do an analysis of the data - the data by selecting products - products that are allowed to be sold by online. Later stages is to design and build online store website pages to be uploaded and accessed via internet which will be the place for promotion and sales of Small and Medium Industries (IKM) products in Tegal City by online. The output product of this research will be one of the efforts in helping to increase the Small and Medium Industries (IKM) income of Tegal City Keywords: Online shop, Small and Medium Industries (IKM), Tegal city